A, MENGUNGKAP EGALITERIANISME DALAM KONSEP AL-MUSAWAH DALAM AL-QUR’AN DAN AL-SUNNAH - Dhani, Kurniawan Ramadhani. M.E (UIN Kiai Haji Achmad Siddiq Jember, 2024)
Social disparities based on ethnicity, culture, skin color, and lineage are common realities globally, including racial discrimination in the West and cultural differences in various regions. Islam, as a religion that emphasizes human equality, prohibits all forms of discrimination. In Islamic teachings, all humans are equal, with superiority determined solely by their conduct. The Qur'an and Sunnah emphasize the importance of equality in human life. The concept of al-musawah, rooted in Islamic teachings, instills egalitarian values in society at large as a response to various forms of discrimination and feudalism based on lineage commonly found in communities. This study examines the concept of al-musawah from the perspective of the Qur'an and Sunnah, its historical context, and its correlation with humanism. Using documentation and historical methods with a sociological approach, this research concludes: 1) Al-musawah is a concept of equality that fosters egalitarian values in individuals and groups. 2) Historically, this concept emerged as a reaction to discriminatory and feudal practices based on lineage. 3) The concept of al-musawah is closely related to humanism, as both uphold human dignity regardless of ethnicity, culture, or lineage. Key Word : al-musawah - humanisme - Egaliterianisme.